Определение неблагоприятного исхода беременности с использованием дискриминантного анализа - Высоцкая, Е. В.; Порван, А. П.; Пойменова, А. А.; Коровай, С. В.; Стеценко, П. И. (My University, 2015)
Работа посвящена определению неблагоприятного исхода беременности с использованием дискриминантного анализа, который позволяет повысить эффективность диагностики и прогнозирования данного состояния за счет улучшения точности определения вероятного исхода, которая достигается получением информативных, прогностически значимых показателей. Использование предложенного подхода даст возможность своевременно проводить профілактику и лечение прерывания беременности. Робота присвячена визначенню несприятливого результату вагітності з використанням дискримінантного аналізу, який дозволяє підвищити ефективність діагностики та прогнозування даного стану за рахунок поліпшення точності визначення ймовірного результату, яка досягається отриманням інформативних, прогностично значимих показників. Використання запропонованого підходу дасть можливість своєчасно проводити профілактику і лікування переривання вагітності. The article is devoted to determination of adverse pregnancy outcomes, using discriminant function analysis, which improves the efficiency of diagnosis and prognosis of this condition by improving the accuracy of determining the likely outcome, which is achieved by obtaining informative, prognostic significant signs. The calculation of diagnostic coefficient values by the selected method allows revealing 6 significant characteristics of protein, carbohydrate, nucleic acid and mineral metabolism and canonical coefficients to determine the pregnancy outcome. The use of discriminant functions and the most significant characteristics allows synthesizing a new mathematical model for determining the pregnancy outcome, which allows describing the condition of the patient. The validity of the synthesized mathematical model has been confirmed by independent testing factors on sample examination with classification accuracy for which amounted to 95,8 %. This method has several advantages: takes into account the variability of parameters included in the model, considering the totality of all the prognostic value and indicates the proportion of the impact of each characteristic on the formation of the severity of the condition. The results provide a timely opportunity to choose the optimal treatment and care of women with threatened miscarriage.
Keywords: дискриминантный анализ; беременность; преждевременные роды